Atypical antipsychotics induce human osteoblasts apoptosis via Wnt/β-catenin signaling - Peifan Li; Yiming Wang; Xingde Liu; Zhen Zhou; Jun Wang; Haiyan Zhou; Lei Zheng; Lixia Yang (BMC, 2019)
Abstract Background There is evidence that atypical antipsychotics (APs) increase risk of osteoporosis in schizophrenia patients, however the mechanism is unclear. The aim of the study was to explore the molecular mechanisms about Wnt/β-catenin signal pathway underlying the osteal side effects of APs. Methods We cultured human osteoblast cell line hFob1. 19 (OB) treatments with olanzapine, risperidone, amisulpride, aripiprazole or resveratrol in vitro. OB cells viability was detected by cell viability assay. OB cells apoptosis was analyzed by flow cytometry (FCM). Further apoptosis-related marker and β-catenin expression was analyzed by Western blot and Immunofluorescence analysis. Results Compared with the control group, proliferation of OB cells decreased and apoptosis rates of OB cells increased significantly in APs group (p < 0.05). There were a reduced level of Bcl-2, Mcl-1 (antiapoptotic marker) and an elevated level of Bax, Cleaved-Caspase3 (proapoptotic marker) in APs group (p < 0.05). Simultaneously, β-catenin expression decreased in cytoplasm and nucleus (p < 0.05). Compared with the just APs group, the apoptosis rates decreased and β-catenin expression increased significantly in resevratrol combined with APs group (p < 0.05). Correlation analysis showed positive correlation between β-catenin expression and the apoptotic rate in OB cells (r = − 0.515, p < 0.05). Conclusions APs cause OB cells apoptosis relating to Wnt/β-catenin signaling while resevratrol could reverse this phenomenon. Our study could lay the foundation for overcoming the APs-induced osteal side effects to improve the life quality of schizophrenia patients.